Editorial - Santos, Zélia Maria de Sousa Araújo (Rev Rene, 2006)
In recent years the nursing scientific production has grown substantially, covering various themes and various levels of health care. Possibly, this fact is a result of the advancement and expansion of Postgraduate courses in Nursing, which enabled the formation of groups and lines of research and which somehow motivate researchers to produce scientific articles in order to feed these lines . Disclosure of this production is conveyed predominantly by nursing journals available in considerable quantity. However, the strengthening of these journals is essential and urgent, requiring simultaneous support of educational institutions and services, through the planning of strategies for scientific production increase of high level.